2023
DOI: 10.3390/nu15030643
|View full text |Cite
|
Sign up to set email alerts
|

Pathogen-Specific Benefits of Probiotic and Synbiotic Use in Childhood Acute Gastroenteritis: An Updated Review of the Literature

Abstract: Probiotics represent viable microorganisms which are found within the normal gut microbiota, that exert strain-specific benefits in the management of several gastrointestinal disorders in children, including acute gastroenteritis. This review aims to evaluate the pathogen-specific role of probiotic supplementation in childhood diarrhea. A search of scientific databases was conducted to identify studies which investigated efficacy of probiotics and synbiotics in influencing outcome of acute gastroenteritis of k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 101 publications
0
3
0
Order By: Relevance
“…The findings of the current study showed that the statistically significant differences were illustrated between the probiotic study and control groups regarding experience of vomiting where less than half of children in the probiotic study group didn't experience vomiting on the first day and this percentage increased on the second and third day compared to the percentages of children in control group. This could be explained in the light of, the probiotic intake increased the level of Bile Salt Hydrolase generating bacteria, which produced free bile acids that enhancing gastrointestinal motility and metabolism and it also have the antiinflammatory and metabolic effects (Săsăran, 2023;Bourgin et al,2021). Liu et al, (2021) who studied the effect of probiotics on improvement of gastrointestinal function also support the results of the present study were mentioned that probiotic intake significantly reduced frequency of vomiting.…”
Section: Discussionmentioning
confidence: 99%
“…The findings of the current study showed that the statistically significant differences were illustrated between the probiotic study and control groups regarding experience of vomiting where less than half of children in the probiotic study group didn't experience vomiting on the first day and this percentage increased on the second and third day compared to the percentages of children in control group. This could be explained in the light of, the probiotic intake increased the level of Bile Salt Hydrolase generating bacteria, which produced free bile acids that enhancing gastrointestinal motility and metabolism and it also have the antiinflammatory and metabolic effects (Săsăran, 2023;Bourgin et al,2021). Liu et al, (2021) who studied the effect of probiotics on improvement of gastrointestinal function also support the results of the present study were mentioned that probiotic intake significantly reduced frequency of vomiting.…”
Section: Discussionmentioning
confidence: 99%
“…These recommendations are grounded on weak evidence [ 44 ]. A lower level of evidence supports the use of L. reuteri for the same purpose, while a recommendation advises against the use of Bacillus clausii, as well as the combination of L. reuteri and L. helveticus in childhood diarrhea, in alignment with their preceding publications [ 45 , 46 ]. The authors refrained from offering specific guidance for diarrhea with a confirmed etiology and recognized the potential impact of rotavirus vaccine coverage on their examination of previously published data [ 45 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…The gut microbiota is crucial to human health, and its condition is related to many childhood diseases (6). Probiotics are a combination of living bacteria and yeast, including the well-known strains of Lactobacillus acidophilus, Bifidobacterium lactis, and L. brevis (4,7). Probiotics are now defined as live microorganisms that, when administered in adequate amounts, confer a health benefit on the host by the Food and Agriculture Organization of the United Nations and the World Health Organization (FAO/WHO) (8).…”
Section: Introductionmentioning
confidence: 99%